Interspecific and intraspecific variation in corolla tube length in Pedicularis species achieved by both cell anisotropy and division. Issue 3 (3rd March 2017) - Wang, Xiang‐Ping; Huang, Shuang‐Quan
Abstract: The association between plants with long corolla tubes and pollinators with long tongues has evolved repeatedly in diverse pollination systems. However, the morphogenesis of long corolla tubes involved in diverse plant groups remains largely unexplored, limiting our understanding of the evolution and maintenance of long corolla tubes. Corolla tubes of Himalayan Pedicularis species exhibit striking length diversity, ranging from less than 10 mm to more than 120 mm. We investigated the role of cell division and cell expansion in determining the corolla tube morphology in eight Pedicularis species and in an experimental population of P. siphonantha Don in which corolla tubes were elongated under shading and watering treatments. Among species, the corolla tube length was positively correlated with both cell number and cell length but not cell width. Our analyses of intraspecific variation in corolla tube length indicated that it was positively correlated with cell length in all eight species but with cell number in only four of the species, indicating that corolla tube development in Pedicularis generally involves anisotropic cell expansion. The elongation of corolla tubes in P. siphonantha under experimental conditions was caused by the anisotropic elongation of cells; cell number of tube‐elongated flowers was not significantly increased. Our results showed that intraspecific variation in corolla tube length in Pedicularis species was largely attributable to changes in cell anisotropy, but the evolutionary innovation underlying the rapid radiation of Pedicularis corolla tubes was attributable to both cell division and cell expansion.